Profile of Safety Factor (SF) Potential Liquifaction based on CPT Data using GIS & Surfer Applications - Poppy Maghfirah (Lowland Technology International, 2021)
Earthquakes can cause damage to the structure of the soil layer, one type of hazard resulting from an earthquake is liquefaction. Liquefaction is an event where the loose sand soil layer experiences a drastic loss of shear strength due to increased pore water pressure as a result of the occurrence of cyclic stresses in very fast soil vibrations in a short time. This liquefaction potential can be analyzed using Cone Penetration Test (CPT) data by considering the value of earthquake acceleration (pga). This study aims to analyze soil conditions in the event of potential liquefaction using CPT (Cone Penetration Test) data through GIS and Surfer applications, computer applications which serves to analyze and create distribution contours from coordinate data and output data from CPT.